Microbial community composition and biofouling in a forward osmosis membrane bioreactor and a membrane distillation bioreactor - Zhang, Qiaoyun (2014)
The forward osmosis membrane bioreactor (FOMBR) and the membrane distillation bioreactor (MDBR) are two high retention membrane bioreactors (HRMBRs) which allow efficient separation of colloidal and dissolved matters from wastewater, which in turn results in salt accumulation in the bioreactor. These reactors provide a novel environment for resident microorganisms that play a crucial role in the degradation of pollutants. Membrane biofouling is a major problem for conventional membrane bioreactors (MBRs). However, the propensity for membrane fouling in FO and MDBRs is unknown. Therefore, this study aimed to characterize the microbial community and membrane fouling in an FOMBR and in an MDBR system.